AUTOMOBILE INDUSTRY IN THE REPUBLIC OF UZBEKISTAN AND BUSINESS DEVELOPMENT TENDENCIES - Baxromjonova Dilnoza; Muhammadjonov Azizbek; Sarvarbek Azimov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: It is known that the acceleration of socio-economic development in Uzbekistan,structural as the priorities of economic liberalization deepening of changes, leading sectors of the national economy its competitiveness due to modernization and diversification increasing, ensuring the balance and stability of the national economy, its increasing the share of industry, small business and private entrepreneurship in the structure, modernization of production, technically and technologically policy of renewal, promotion of localization of production continuation and, above all, consumer goods and components substitution of imports, expansion of intersectoral industrial cooperation and field to industry, information and communication technologies to the management system implementation is set.